A new interpretation of TCM pulse diagnosis based on quantum physical model of the human body - Shuna SONG; Zhensu SHE (KeAi Communications Co., Ltd., 2022)
Following the quantum theory-based physical model of the human body, a new interpretation of the traditional Chinese medicine (TCM) principle of "Cunkou reads viscera" is presented. Then, a Gaussian pulse wave model as a solution to the Schrodinger equation is shown to accurately describe 19 different pulse shapes, and to quantitatively capture the degree of Yin-Yang attributes of 13 pulse shapes. Furthermore, the model suggests using pulse depth and strength as leading-order quantity and pulse shape as first-order quantity, to characterize the hierarchical resonance between the human body and the environment. The future pulse informatics will focus on determining an individual's unique quantum human equilibrium state, and diagnose its health state according to the pulse deviation from its equilibrium state, to truly achieve the high level of TCM: "knowing the normal state and reaching the change".